PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN YANG BEROBAT DIINSTALASI GAWAT DARURAT RUMAH SAKIT UMUM SANGATTA - SUYATIN3, HUSNI THAMRIN 1, LCA ROBIN JONATHAN2 (EKONOMIA, 2016)
This study was conducted to examine the effect of level of service quality to the Emergency Room Patient Satisfaction.The sample used in this study of 100 respondents. The method of sampling using purposive sampling. Data analysis method used is quantitative analysis using validity and reliability test, classic assumption test, F test, the coefficient of determination, t test and multiple regression analysis.By using multiple regression analysis can be concluded that the direct evidence variable positive and significant impact on customer satisfaction with the value of significance (P value) of 0.003 <0.05. While reliability but not significant positive effect on customer satisfaction with the value of significance (P value) amounted to 0.440> 0.05. Assurance but not significant positive effect on customer satisfaction with the value of significance (P value) amounted to 0.164 <0.05. Responsiveness but not significant positive effect on customer satisfaction with the value of significance (P value) amounted to 0.339> 0.05.For no empathy and no significant positive effect on customer satisfaction with the value of significance (P value) amounted to 0.623> 0.05. Simultaneously direct evidence, reliability, assurance, responsiveness and empathy significantly influence consumer satisfaction with F count equal to 11.186 with the number of significance (P value) of 0.000 <0.05. The resulting coefficient of determination is 0.34, which means a 34 percent change in consumer satisfaction variables explained by changes in variable direct evidence, reliability, assurance, responsiveness and empathy together, while the remaining 66 percent is explained by other variables not included in the this research